Pandemics, epidemics and inequities in routine childhood vaccination coverage: a rapid review - Samantha Johnson; Nick Spencer; Rita Nathawad; Emmanuele Arpin (BMJ Paediatrics Open, 2020)
Inequity in routine childhood vaccination coverage is well researched. Pandemics disrupt infrastructure and divert health resources from preventive care, including vaccination programmes, leading to increased vaccine preventable morbidity and mortality. COVID-19 control measures have resulted in coverage reductions. We conducted a rapid review of the impact of pandemics on existing inequities in routine vaccination coverage. PICO search framework: Population: children 0–18 years; Intervention/exposure: pandemic/epidemic; Comparison: inequality; Outcome: routine vaccination coverage. The review demonstrates a gap in the literature as none of the 29 papers selected for full-paper review from 1973 abstracts identified from searches met the inclusion criteria.